DUS characterization of muskmelon (Cucumis melo) varieties - CHOUDHARY, B R; PANDEY, S; RAO, E S; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2015)
The present study was carried out for morphological characterization of twelve reference varieties of muskmelon (Cucumis melo L.) collected from ICAR institutes and SAUs to validate DUS testing guidelines using plant descriptors adopted from the DUS guidelines of PPV and FRA. Among 34 morphological characters studied, 19 were visually assessed and 15 were measured. The fruit shape in longitudinal section was expressed as ovate (MHY 5), elongated globe (Arka Rajhans), oblate (GMM 3, Kashi Madhu) and obovate (Durgapura Madhu). The rind colour of fruit have been grouped as yellow (Kashi Madhu), yellow green (Durgapura Madhu) and orange (Arka Jeet). The sutures on fruit surface were found to be absent in Arka Jeet, MHY 3 and present in Hara Madhu, Kashi Madhu varieties. With respect to netting on fruit surface the varieties have been grouped as absent of netting (Arka Jeet, MHY 5) and moderate netting (RM 50, Punjab Sunehri). The flesh colour was expressed as creamish white (Arka Jeet), grey orange (GMM 3), yellowish green (Durgapura Madhu), green (Hara Madhu) and orange (Kashi Madhu). Under results, no intra-varietal variation was observed for any of the visual characteristics examined. Further, the expression of characters in different varieties remained same for the three consecutive years confirming the uniformity and stability of the varieties for visual characteristics. The varieties were grouped into different categories for each character based on 34 descriptors which may be used as reference varieties. Identified 6 traits as grouping traits, viz. sex expression (at full flowering), fruit shape in longitudinal section, rind colour of fruit, sutures on rind, surface netting of fruit and fruit flesh colour. The morphological characterization of extant varieties was completed to establish distinctness of the candidate variety from all other varieties to utilize these varieties as reference material for protection of other varieties under PPV&FR Act.